Supplementation with RD antigens enhances the protective efficacy of BCG in tuberculous mice - Kalra, Mamta (Clinical immunology (Orlando, Fla.), 2007)
Different combinations of ESAT-6, CFP-10, CFP-21, MPT-64, encoded by RD1 and RD2 of Mycobacterium tuberculosis were evaluated on the basis of antigenicity in PPD positive TB contacts and immunogenicity in C57BL/6J mice immunized with the combination of all four RD antigens. The peripheral blood mononuclear cells of TB contacts showed maximum recognition in response to the combination of ESAT-6+MPT-64 in terms of predominant lymphoproliferation, IFN-gamma levels and the number of responders. On the contrary, the combination of ESAT-6+CFP-21+MPT-64 was found to be most immunogenic based on both T-cell and antibody responses in immunized mice. Prophylactic potential of the selected combinations was assessed as supplementation vaccines to BCG against intravenous challenge with M. tuberculosis in mice. BCG supplementation with the selected combinations resulted in significantly greater protection as compared to BCG alone against experimental tuberculosis and thus appears to be a promising approach to enhance the protective efficacy of the existing vaccine